The International encyclopedia of communication - Donsbach, Wolfgang 1949- (Blackwell Pub., 2008)
Collection of 1,339 original entries, spanning the scholarship, evidence, and methodology of communication research. Coverage of theories, media and communication phenomena, research methods, problems, concepts, and geographical areas in this interdisciplinary field. Editorial areas include: communication theory and philosophy, interpersonal communication, journalism, intercultural and intergroup communication, media effects, strategic communication/PR, communication and media law and policy, media systems in the world, and communication and technology.